Discrepancies in information technology strategic alignment in healthcare. (3rd July 2020) - Farah, Soleil; Bonnet, Marc; Damaj, Kamar
Information technology contributes significantly to the healthcare industry. Healthcare IT, if efficiently managed, can decrease expenses; enhance hospitals processes, patient satisfaction and care. From this perception, the necessity to improve information systems management becomes a significant governance and structural concern in hospitals. Therefore, it is fundamental to set an appropriate IT strategy, provide means to manage and implement it. IT strategic alignment is crucial to developing and maintaining all kind of information and communication that supports patients' treatment processes, business operations and ameliorates organisational social and economic performances. This study is a kind of action research project, and more specifically a qualimetrics intervention research methodology, a transformative approach, conducted in a private hospital in Lebanon. As technical systems are turning out to be more complex and indispensable to healthcare organisations, there is a rising awareness to preserve a sustainable environment, through maintaining intellectual, social and operational strategy of the organisation.